2008
DOI: 10.2478/s11658-007-0055-5
|View full text |Cite
|
Sign up to set email alerts
|

The genes and enzymes involved in the biosynthesis of thiamin and thiamin diphosphate in yeasts

Abstract: Thiamin (vitamin B1) is an essential molecule for all living organisms. Its major biologically active derivative is thiamin diphosphate, which serves as a cofactor for several enzymes involved in carbohydrate and amino acid metabolism. Important new functions for thiamin and its phosphate esters have recently been suggested, e.g. in gene expression regulation by influencing mRNA structure, in DNA repair after UV illumination, and in the protection of some organelles against reactive oxygen species. Unlike high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
32
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 28 publications
1
32
0
Order By: Relevance
“…Its synthesis has been well characterized in bacteria, but knowledge of the early steps of de novo synthesis in yeast is less complete (25). Yeast first separately synthesizes two precursors, 5-(2-hydroxyethyl)-4-methylthiazole phosphate (HET-P) and 4-amino-5-hydroxymethyl-2-methylpyrimidine diphosphate (HMP-PP) through poorly understood mechanisms.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Its synthesis has been well characterized in bacteria, but knowledge of the early steps of de novo synthesis in yeast is less complete (25). Yeast first separately synthesizes two precursors, 5-(2-hydroxyethyl)-4-methylthiazole phosphate (HET-P) and 4-amino-5-hydroxymethyl-2-methylpyrimidine diphosphate (HMP-PP) through poorly understood mechanisms.…”
mentioning
confidence: 99%
“…HMP-PP is synthesized in yeast cells from histidine and pyridoxal-5-phosphate (PLP; vitamin B6), thus providing a link between the synthesis pathways for these two soluble B vitamins. The substrates for HET-P synthesis include cysteine, glycine, and D-pentulose-5-phosphate (25). More recently, synthesis of the HET-P moiety was shown to also proceed through an advanced intermediate generated by the Thi4 protein in a reaction that consumes NAD ϩ as a substrate, releasing nicotinamide (NAM) as a by-product (12).…”
mentioning
confidence: 99%
“…It was discovered in 1911 by Casimir Funk, isolated in 1932 from yeast and synthesized in 1935 [2]. Though occurring in all living cells, only prokaryotes and a few eukaryotes, such as fungi and plants, are able to de novo synthesize thiamine [3,4]. Because thiamine-dependent enzymes are crucial for central metabolic pathways, changes in thiamine regulation can affect many different processes.…”
Section: Introductionmentioning
confidence: 99%
“…Labeling studies in S. cerevisiae have demonstrated that the thiamine-thiazole is synthesized from an unidentified five-carbon carbohydrate, glycine, and cysteine [12]. This biosynthesis has not yet been reproduced in vitro, but a metabolomic study has recently proposed NAD + (nicotinamide adenine dinucleotide) as the early source of a five-carbon carbohydrate and the advanced intermediate as an ADP adduct of 5-(2-hydroxyethyl)-4-methylthiazole-2-carboxylic acid [4,14]. The gene encoding THI1 protein was originally cloned due to its capacity to complement Escherichia coli mutant line BW535 (xth, nfo and nth genes), which is defective in DNA base excision repair pathways [13].…”
Section: Introductionmentioning
confidence: 99%
“…These moieties are synthesized by two separate branches regardless of the organism and require about 16 genes for their de novo biosynthesis (1,2) (Fig. 1A).…”
mentioning
confidence: 99%